DESORPSI β-KAROTEN MINYAK KELAPA SAWIT (CRUDE PALM OIL) DARI KARBON AKTIF MENGGUNAKAN ISOPROPANOL - Nurul Aini, Olyvia Putri Wardhani, Iriany (Universitas Sumatera Utara, 2016)
The aim of the research is to study the ability of isopropyl alcohol in the desorption of β-carotene and to obtain kinetic model and desorption isoterm which is suitable in β-carotene desorption. The main material used were isopropyl alcohol and activated carbon containing β-carotene. The variabels used in this research are desorption temperature, activated carbon concentration and parameter observed is concentration of β-carotene in isopropyl alcohol. In the desorption process, activated carbon which adsorp β-carotene was soaked in isopropyl alcohol. To review the desorption kinetics, this research was carried out in various temperature such as 40 oC, 50 oC, and 60 oC. In desorption isoterm process is, various mass of activated carbon was used. Desorption process will be analyzed at spesified time. This research used the first order of desorption kinetics model. The desorption constant rate obtained for 40 oC, 50 oC, and 60 oC are 0,013, 0,014, and 0,036 minute-1 with activation energy is 0,226 kkal/mol. The maximum desorption percentage obtain is 41,94 %. The desorption isoterm model which fit with the β-carotene desorption was Langmuir isoterm model with constanta value 1,2077 L/mg and -0,2218.